Hepatitis E seroprevalence and viremia rate in immunocompromised patients: a systematic review and meta‐analysis. (13th February 2021) - Buescher, Gustav; Ozga, Ann‐Kathrin; Lorenz, Eva; Pischke, Sven; May, Jürgen; Addo, Marylyn M.; Horvatits, Thomas
Abstract: Background and Aims: Hepatitis E is an infectious disease of the liver caused by the hepatitis E virus (HEV). Immunocompromised patients present a particular risk group, as chronification of hepatitis E leading to life‐threatening cirrhosis occurs when these patients are infected. Therefore, this study aims to estimate and compare the anti‐HEV seroprevalence and the rate of HEV RNA positivity in transplant recipients and patients with human immunodeficiency virus (HIV). Methods: This systematic review and meta‐analysis involved a literature search (PubMed, Scopus; 1, 138 studies) including 120 studies from 1996 to 2019, reporting anti‐HEV seroprevalence and/or HEV‐RNA positivity. Statistical analysis was performed using a linear mixed‐effects meta regression model. Results: Anti‐HEV seroprevalence in 14 626 transplant recipients ranged from 6% (95% CI: 1.9‐17.2) to 29.6% (95% CI: 21.6‐39.) in different commercially available assays and did not differ significantly compared to 20 825 HIV positive patients (range: 3.5% (95% CI: 0.9‐12.8) – 19.4% (95% CI: 13.5‐26.9). In contrast, HEV‐RNA positivity rate was significantly higher in transplant recipients than in HIV positive patients (1.2% (95% CI: 0.9‐1.6) vs 0.39% (95% CI: 0.2‐0.7); P ‐value = 0.0011). Conclusion: Anti‐HEV seroprevalence did not differ significantly between transplant recipients and HIV positive patients. Interestingly, rates of HEV‐RNA positivity, indicating ongoing infection, were significantly higher in transplant recipients. These findings demonstrate that transplant patients have an elevated risk of chronic infection in comparison to HIV patients at comparable risk of HEV‐exposure.